GAMBARAN TINGKAT KECEMASAN PASIEN GAGAL GINJALMENJALANI TERAPI HEMODIALISA DI RUMAH SAKIT ISLAM SITI RAHMAH PADANG TAHUN 2017 - Rika yoni (Menara Ilmu, 2018)
Hemodialysis is a high technology as a substitute for kidney function to remove certainresidual metabolism or toxins from human blood circulation through semi permiabelmembrane as blood and dialysis fluid in artificial kidney where diffusion, osmosis andultra filtration process occurs. From WHO data recorded the world's kidney failurepatients more than 500 million people, is the disease ranked 12th highest cause of death.Based on data from the Association of Nephrology of Indonesia in 2011 there are about12,500 patients with renal failure undergoing routine hemodialysis therapy. Riskesdas2013 shows the prevalence of renal failure in West Sumatra by 0.2%. The year 2014 inWest Sumatra recorded 368 patients with kidney failure and 191 of them undergoinghemodialysis. The purpose of this study to determine the picture of anxiety levels ofpatients with renal failure undergoing hemodialysis therapy at Siti Rahmah PadangIslamic Hospital.The type of research used is descriptive. The study was conducted in March to April 2017,the study population was 30 people. The sample in this study were 30 respondents,sampling technique using total sampling. The data were collected using a HARSquestionnaire to find out anxiety levels of patients undergoing hemodialysis therapy.The result of this research was 1 patient (3.3%) had mild anxiety level, moderate anxietylevel 5 patients (16.7%), severe anxiety level as many as 18 patients (60.0%), and severeanxiety level as many as 6 patients (20.0%)The conclusion of this study is that patients who undergo hemodialysis therapy in RSI SitiRahmah Padang many who experience the level of severe anxiety. So the researcherssuggest to hospital officials in order to reduce anxiety patients by providing counselingand counseling.Keywords: Patient Anxiety Level With Kidney Failure, Hemodialysis Therapy.